Clinical and histological criteria for sex cord ovarian stromal tumors - A. М. Beishembaev; K. I. Zhordania (Акушерство, гинекология и репродукция, 2020)
Aim: to identify clinical and histological criteria for sex cord ovarian stromal tumors (OSTs).Materials and Methods. The retrospective non-comparative study was based on the main inclusion such as histologically verified sex cord OSTs. A standard examination algorithm was analyzed (ultrasound, blood tests, CT or MRI of the abdominal and pelvic organs). All clinical data were obtained from patients treated and monitored in clinical units at the Blokhin National Medical Research Center of Oncology and the National Center of Oncology and Hematology of the Kyrgyz Republic.Results. Data were obtained on the frequency of necrobiotic changes, malignancy, disease stages and their impact on survival in 456 patients. The 10-year survival rate for OSTs patients with vs. without intra-tumor necrobiotic changes was significantly lower (17.2 % and 78.1 %, respectively).Conclusion. The main factors of unfavorable prognosis in patients with granulosa cell ovarian tumors were disease stage and intra-tumor necrobiotic changes.